Navigating Institutional Pressure and Individual Resistance in Online Game Consumption: Demographic and Playing Characteristics Perspective - Mahardika, Andika; Runturambi, Arthur Josias Simon; Revindo, Mohamad Dian (Sociology Department Of Syiah Kuala University, 2025)
The integration of computing technology and its widespread adoption by society has transformed online games from solitary and individualistic activities into socially embedded environments. This transformation is driven by institutional pressures that shape consumption behavior, while also eliciting varying levels of individual resistance. These patterns of social interaction are significantly influenced by demographic and individual playing characteristics. This study aims to examine how these characteristics affect consumption behavior in online games. Adopting principal component analysis and regression methods based on previous research, the study found that institutional influence is strongly associated with playing duration and the desire to become a professional player. Meanwhile, individual resistance is influenced by age, playing time, and the same desire. Conducted in Jakarta, the findings reveal that structural pressure is primarily shaped by playing characteristics, while resistance is affected by both demographics (specifically age) and individual playing characteristics.